Reconstruction of tracheocutaneous fistula with a rhomboid flap - Kazuya Kashiyama (Respiratory Medicine Case Reports, 2019)
Various complications associated with tracheal stomas have been reported, including mechanical trauma to the peristomal skin, infection, folliculitis, granuloma, and fistula. Among them, a tracheocutaneous fistula generally requires surgical repair. A number of methods have been reported for reconstruction of fistulas using musculocutaneous flaps or free flaps. However, those surgical techniques are all designed for complete close of the tracheocutaneous fistula and stoma, while partial closure of the stoma around the indwelling tracheal tube is not well described in the literature. We report on the use of a rhomboid flap for partial closure of a tracheal stoma. The rhomboid flap is a local flap that is frequently used by plastic surgeons because of its broad applications and not being very invasive. This is a low invasive and simple technique for partial closure of an excessively enlarged stoma. Keywords: Tracheal stoma, Rhomboid flap, Limburg flap